Attitudes towards languages and cultures of young Polish adolescents in Iceland - Berman, Robert , 1949-; Samuel C. Lefever 1954-; Anna Katarzyna Wozniczka 1983- (2011)
This preliminary study examines the attitudes to Icelandic, Polish and English languages and cultures of four young Polish adolescents in Iceland. Its aim was to establish their motivation to learn Icelandic as well as to maintain their heritage language and culture. Also investigated was whether English was an impediment to their acquisition of Icelandic. Interviews, in Polish and Icelandic, were undertaken. It was found that the adolescents were motivated to learn Icelandic, to integrate into Icelandic society and to maintain their Polish heritage. In this sense, they lived in “two worlds,” maintaining close bonds with their Polish heritage, while also integrating into Icelandic society. English was not impeding their integration. Unlike some of their parents, they could imagine living in Iceland in the future, as they saw Iceland as a place where they could “fulfill themselves.” Þessi forkönnun rannsakar viðhorf fjögurra pólskra unglinga til íslenskrar, pólskrar og enskrar tungu og menningar. Markmiðið var að greina áhugahvöt þeirra til að læra íslensku og halda við eigin tungu og menningararfi. Einnig var rannsakað hvort enska stæði í vegi fyrir því unglingarnir læri íslensku. Tekin voru viðtöl á pólsku og íslensku. Í ljós kom að unglingarnir vildu læra íslensku, samlagast íslensku samfélagi og varðveita pólskan menningararf. Að þessu leyti lifðu þeir í tveimur heimum, með því að halda við nánum tengslum við pólskan menningararf og laga sig um leið að íslensku samfélagi. Enska stóð ekki í vegi fyrir þeirri samlögun. Ólíkt sumum foreldra þeirra gátu þeir hugsað sér að búa á Íslandi í framtíðinni enda litu þeir á landið sem stað þar sem þeir gætu uppfyllt væntingar sínar um sjálfa sig.